Integrating Clarke's discourse analysis and mapmaking approaches in Print's situation analysis - De Los Reyes, Ma. Cristina B.
The try-out and revision of Print's SA in a multicultural school deconstructed the situation into curriculum intent, content, learning activities, evaluation, and factors that influence the curriculum. Following an exploratory sequential mixed method design. Print's four stage SA was integrated with Clarke's discourse analysis and mapmaking approaches. The result yielded data that provided contextual understanding of the specific and unique situation. Because the multicultural school and its curriculum are highly heterogeneous in nature, data was analysed to reveal agreements and disagreements in stakeholders’ perspectives. More importantly, the revised model helped discover crucial curriculum elements that are either present or inadvertently taken for granted during the school's past SA for curriculum planning activities. This paper recommends continuous effort to improve and revise Print's SA model depending on the nature of the situation being analysed.